Azaacenes Bearing Five‐Membered Rings. Issue 51 (10th August 2018) - Ganschow, Michael; Koser, Silke; Hodecker, Manuel; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F.
Abstract: We report the synthesis of processible (dihydro)pyracyclene‐ and acenaphthylene‐substituted azaacenes using condensation reactions in solution. The targets are characterized via cyclic voltammetry, X‐ray crystallography, UV/Vis, fluorescence spectroscopy and DFT/NICS calculations. Formal hydrogenation of the annulated five‐membered ring surprisingly alters emission in the solid‐state as a consequence of modulation of aromaticity and HOMO–LUMO overlap. Five highly fluorescent, crystalline azaacenes were investigated as emitters in organic light‐emitting diodes, and their performance with respect to luminance and efficiency was compared to that of structurally related azaacenes. Abstract : Illuminate by hydrogenation : A series of novel azaacenes containing saturated and unsaturated five‐membered rings show dramatically different emission characteristics. The saturated azaacene is a useful OLED emitter with high luminance.